Cheating Behavior Viewed From Conformity In High School Students Gajah Mada School Medan: Perilaku Menyontek Ditinjau Dari Konformitas Pada Siswa SMA Sekolah Gajah Mada Medan - Sherly, Sherly (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine the relationship between conformity and cheating behaviour. The hypothesis of this study states that there is a positive relationship between conformity and cheating behaviour, with the assumption that the higher the conformity has, the higher the cheating behaviour, and conversely the lower the conformity has, the lower cheating behaviour. The participans of this study were 105 high school student in Gajah Mada School . The sampling technique used is disproportionate stratified random sampling. Data were obtained from a scale to measure conformity and cheating behavior. The calculation was performed using test requirements analysis (assumption), which consists of normality distribution test and linearity relationship test. Data were analyze by Product Moment Correlation with SPSS 20 for windows. The results of data analysis showed that the correlation coefficient was 0,659 (p<0.05). It showed that there is a positive relationship between conformity and cheating behaviour. These results indicate that the contributions of conformity variable to cheating behaviour was at 43,4 percent, while the remaining 56,6 percent is influenced by other factors not examined. Based on these results it is concluded that the hypothesis stating there is a positive relationship between conformity and cheating behaviour, is acceptable.